2011
DOI: 10.1099/ijs.0.017418-0
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus kimchicus sp. nov., a β-glucosidase-producing bacterium isolated from kimchi

Abstract: Lactobacillus kimchicus sp. nov., a b-glucosidaseproducing bacterium isolated from kimchi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…In this study, we used L. plantarum for the microbial conversion of ginsenosides in red ginseng. L. plantarum has been traditionally used for kimchi fermentation and is considered to be a food-grade microorganism [24]. Using this bacteria, Kim et al [25] found that fermented red ginseng contains a much higher concentration of total ginsenosides and metabolites, especially Rh1, Rh2, Rg5, Rk1, Rg2, Rg3, and compound K. Of note, FRG has enhanced immunological activities compared to red ginseng [26].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used L. plantarum for the microbial conversion of ginsenosides in red ginseng. L. plantarum has been traditionally used for kimchi fermentation and is considered to be a food-grade microorganism [24]. Using this bacteria, Kim et al [25] found that fermented red ginseng contains a much higher concentration of total ginsenosides and metabolites, especially Rh1, Rh2, Rg5, Rk1, Rg2, Rg3, and compound K. Of note, FRG has enhanced immunological activities compared to red ginseng [26].…”
Section: Discussionmentioning
confidence: 99%
“…1, DKL121 showed the highest β-galactosidase activity within selected strains but its activity was lower than commercial strain, ST-body1. Liang et al (2011) reported that a β-galactosidase producing bacterium isolated from Kimchi and was identified as L. platarum group. To evaluate the activity in β-galactosidase of selected strains, changes in sugar contents of fermented milk were determined (Table 3).…”
Section: Enzyme Activitiesmentioning
confidence: 99%
“…The microorganisms involved in Kimchi fermentation include about 200 species of bacteria (Liang et al . ).…”
Section: Introductionmentioning
confidence: 97%